Results of geochemical research of the manifestations of ore mineralisation in the batholith rocks of the Antarctic Peninsula - G. V. Artemenko; V. G. Bakhmutov; L. M. Bakhmutova (Ukrainian Antarctic Journal, 2012)
In the gabbro intrusions of AP batholith rocks the manifestations of ore mineralization of magnetite, ilmenite and sulphides in connection with intramagmatic dikes and more late gabbro-pegmatites were defined. The elevated concentrations of V, Co, Cu were estimated. А significantly higher content of Cu, U, Th, Sc and REE is observed in gabbros of intramagmatic postintrusion dikes. The Co content in pyrite reaches 3,5 %. The ore mineralization of pyrite, chalcopyrite and magnetite in the granite intrusions is associated with quartz veins of post-tectonic hydrothermal stage and with epigenetic processes in the tectonic faults. The impurities of Ag and As in sulfides from this zones were detected.